(untitled) (Muitas Vozes, 2024)
The work Kosmofonia: Mbyá-Guarani (2006), organized by Guillermo Sequera and Douglas Diegues, is a work that stands out for the quality of its anthropological analysis. The research carried out with the M’byá community along the Paraná River, however, is much more than a simple treatise about such an indigenous culture and its connection with the kósmos. The work explores a peculiar way of approaching the theme, mixing Portuguese, Spanish and Guarani, in what we can consider a “wild Portunhol”. Therefore, this article is based on studies by Benjamin (1967), Gasparini (2012), Jasinski (2021), Catonio (2018) and Molloy (2018), with the aim of analyzing the concept of “living between languages”, as well as relating the text to texts by other authors with a similar approach. This study corroborates the conception of a literary activity exclusive to border regions, in which languages are mixed and reflected in the art and culture of large regions.